PHENOMENON OF SWARM IN VOLCANIC REGION OF VIETNAM SOUTHMIDDLE SEASHORE - Thuc, Pham Van (Vietnam Journal of Marine Science and Technology, 2009)
From  June  2005  up  to  now  in  Vietnam  Southmiddle  Seashore  appeared series of earthquakes (swarm) with weak and middle intensities in which there were four felt at Ho Chi Minh city.  These  earthquakes  occurred  in  the  same  area  where  group  of  active  volcanoes  are located,  at  this  area  Hon  Tro  volcano  group  have  erupted  several  times  in  1880,  1923 … Swarm shows the movement upward  of heat magma flow they will either cause rocks to break or cracks to  vibrate and  forecasts the the appearance of volcanoes in the future. The  characteristics  of  the  earthquakes  in  this  region  are  that  they  have  magnitude about 5 with the hypocenter depth of about 10 to 12 km and the focal mechanism of strike slip